Home body - Kaur, Rupi (Simon & Schuster UK Ltd, 2020)
From the Number One Sunday Times bestselling author of milk and honey and the sun and her flowers comes her greatly anticipated third collection of poetry. Rupi Kaur constantly embraces growth, and in home body, she walks readers through a reflective and intimate journey visiting the past, the present and the potential of the self. Home body is a collection of raw, honest conversations with oneself - reminding readers to fill up on love, acceptance, community, family, and embrace change. illustrated by the author, themes of nature and nurture, light and dark, rest here. I dive into the well of my body and end up in another world everything i need already exists in me there's no need to look anywhere else - home.